Preoperative leptin levels were associated with postoperative acute kidney injury in patients with acute type A aortic dissection - Meiling Cai; Fei Jiang; Yanchun Peng; Sailan Li; Yuling Xie; Liangwan Chen; Yanjuan Lin (Renal Failure)
Objective Acute kidney injury (AKI) is a common surgical complication of acute type A aortic dissection (AAAD) and strongly associated with an unfavorable prognosis. Although elevated leptin levels have been identified as a potential risk factor for chronic kidney disease in middle-aged and elderly individuals, their association with AKI following AAAD surgery remains unknown. This study investigated the association between preoperative leptin levels and postoperative AKI in patients with AAAD.Methods This study included 159 patients with AAAD at Fujian Heart Medical Center. The Kidney Disease: Improving Global Outcomes standards were used to define and classify AKI. The receiver operating characteristic (ROC) curves were used to assess the ability of leptin levels to predict AKI. Binary logistic regression analysis was used to study the association between leptin level and AKI.Results The incidence of AKI was 33.96%. Leptin levels in the AKI group and stage 1, 2, and 3 AKI groups were higher than those in the non-AKI group (p < 0.05). Multivariate analysis revealed that elevated leptin levels were an independent risk factor for AKI (p < 0.001). ROC analysis of leptin detection for AKI showed an area under the curve of 0.71. The risk of AKI in the high-level group (leptin levels ≥3.62 ng/mL) was 3.87 times to the low-level group (leptin levels < 3.62 ng/mL).Conclusion Elevated leptin levels are associated with AKI, and plasma leptin may serve as a potential early blood biomarker for AKI in patients with AAAD.